Qualitative Analyses of ψ-Caputo Type Fractional Integrodifferential Equations in Banach Spaces - Abdo, Mohammed S. (Journal of Advances in Applied & Computational Mathematics, 2022)
In this research paper, we develop and extend some qualitative analyses of a class of a nonlinear fractional integro-differential equation involving ψ-Caputo fractional derivative (ψ-CFD) and ψ-Riemann-Liouville fractional integral (ψ-RLFI). The existence and uniqueness theorems are obtained in Banach spaces via an equivalent fractional integral equation with the help of Banach’s fixed point theorem (B’sFPT) and Schaefer’s fixed point theorem (S’sFPT). An example explaining the main results is also constructed.